Kajian Kemampuan Membaca Permulaan Ditinjau dari Lingkup Keaksaraan pada Siswa Kelas I SD Negeri 51 Sungai Raya - Cica Purwana, Cica; Afryaningsih, Yunika; Farisi, Salman Al (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Reading is the first step for students to understand learning. This research aims to examine initial reading abilities in terms of the scope of literacy in grade 1 students at SD Negeri 51 Sungai Raya. The type of research used is qualitative. The subject of this research was class 1B students with a total of 20 students. The main data used are test sheets and interview sheets. The analysis consisting of data collection, data reduction, data presentasion, data conclusions and data verificayion. Based on the research results, it can be concluded that the initial reading ability of class 1 students in terms of the scope of literacy is said to be good because the focus of the first research was recognizing letters verry wel with a percentage of 87,5% of students’ initial reading ability; the seconf reseatch focus atated that the picture group was very good with a percentage 0f 97,5% of students’ initial reading ability; and the third research focus was reading one’s own name well with a percentage of 87,5% initial reading ability in class 1b students at SD Negeri 51 Sungai Raya